Arctic concentration–discharge relationships for dissolved organic carbon and nitrate vary with landscape and season. Issue Volume 66:Issue S1(2021) Supplement (31st December 2020) - Shogren, Arial J.; Zarnetske, Jay P.; Abbott, Benjamin W.; Iannucci, Frances; Medvedeff, Alexander; Cairns, Sam; Duda, Megan J.; Bowden, William B.
Abstract: Climate change is intensifying the Arctic hydrologic cycle, potentially accelerating the release of carbon and nutrients from permafrost landscapes to rivers. However, there are limited riverine flow and solute data of adequate frequency and duration to test how seasonality and catchment landscape characteristics influence production and transport of carbon and nutrients in Arctic river networks. We measured high frequency hydrochemical dynamics at the outlets of three headwater catchments in Arctic Alaska over 3 years. The catchments represent common Arctic landscapes: low‐gradient tundra, low‐gradient and lake‐influenced tundra, and high‐gradient alpine tundra. Using in‐situ spectrophotometers, we measured dissolved organic carbon (DOC) and nitrate (NO3 − ) concentrations at 15‐min intervals through the flow seasons of 2017, 2018, and 2019. These high‐frequency data allowed us to quantify concentration–discharge (C‐Q) responses during individual storm events across the flow season. Differences in C‐Q responses among catchments indicated strong landscape and seasonal controls on lateral DOC and NO3 − flux. For the two low‐gradient tundra catchments, we observed consistent DOC enrichment (transport‐limitation) and NO3 − dilution (source‐limitation) during flow events. Conversely, we found consistent NO3 − enrichment and DOC dilution in the high‐gradient alpine catchment. Our analysis revealed how high flow events may contribute disproportionately to downstream export in these Arctic streams. Because the duration of the flow season is expected to lengthen and the intensity of Arctic storms are expected to increase, understanding how discharge and solute concentration are coupled is crucial to understanding carbon and nutrient dynamics in rapidly changing permafrost ecosystems.